Chemical Composition and Biological Effects of Artemisia maritima and Artemisia nilagirica Essential Oils from Wild Plants of Western Himalaya - Stappen, Iris; Wanner, Jürgen; Tabanca, Nurhayat; Wedge, David E.; Ali, Abbas; Khan, Ikhlas A.; Kaul, Vijay K.; Lal, Brij; Jaitak, Vikas; Gochev, Velizar; Girova, Tania; Stoyanova, Albena; Schmidt, Erich; Jirovetz, Leopold (Planta Medica, 2014)
Artemisia species possess pharmacological properties that are used for medical purposes worldwide. In this paper, the essential oils from the aerial parts of Artemisia nilagirica and Artemisia maritima from the western Indian Himalaya region are described. The main compounds analyzed by simultaneous GC/MS and GC/FID were camphor and 1,8-cineole from A. maritima, and camphor and artemisia ketone from A. nilagirica. Additionally, the oils were evaluated for their antibacterial, antifungal, mosquito biting deterrent, and larvicidal activities. A. nilagirica essential oil demonstrated nonselective antifungal activity against plant pathogens Colletotrichum acutatum, Colletotrichum fragariae, and Colletotrichum gloeosporioides, whereas A. maritima did not show antifungal activity. Both Artemisia spp. exhibited considerable mosquito biting deterrence, whereas only A. nilagirica showed larvicidal activity against Aedes aegypti. Antibacterial effects assessed by an agar dilution assay demonstrated greater activity of A. maritima essential oil against Staphylococcus aureus and Pseudomonas aeruginosa compared to A. nilagirica.
Keywords: Artemisia nilagirica; Artemisia maritima; Asteraceae; antifungal activity; antibacterial activity; biting deterrence; larvicidal activity